2019
DOI: 10.31025/2611-4135/2019.13771
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Efficiency of Pressurized Solvent Extraction of Oil From Spent Coffee Grounds

Abstract: Spent coffee grounds (SCG) are the main residues of the coffee beverage industry, and a potentially valuable source of energy-dense lipids. The present study investigates the effect of temperature, pressure and duration on the pressurized solvent extraction of lipids from dried SCG to evaluate their impact on oil extraction efficiency, composition and energy content. Solvent extraction trials at elevated temperatures performed by an Accelerated solvent extraction (ASE) unit revealed a beneficial effect of incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previously reported data in the literature indicates that triglycerides and fatty acids are the predominant lipid class found in SCG oils. For instance, Efthymiopoulos et al (2019a) reported TAG concentrations ranging between 39% and 74% whereas fatty acids ranged from 11% to 33%. Meanwhile, diglycerides and monoglycerides were also found in SCG oils but the latter was found in higher amounts (8-23%) than the monoglycerides (0-6%).…”
Section: Lipid Class Compositionmentioning
confidence: 99%
“…Previously reported data in the literature indicates that triglycerides and fatty acids are the predominant lipid class found in SCG oils. For instance, Efthymiopoulos et al (2019a) reported TAG concentrations ranging between 39% and 74% whereas fatty acids ranged from 11% to 33%. Meanwhile, diglycerides and monoglycerides were also found in SCG oils but the latter was found in higher amounts (8-23%) than the monoglycerides (0-6%).…”
Section: Lipid Class Compositionmentioning
confidence: 99%
“…Differences in silverskin lipid content can be partially attributed to factors such as different varieties of coffee, the origin of coffee beans, coffee-growing conditions (climate, time of harvest), and processing methods (wet or dry processing and roasting) [40,50,51]. Gottstein et al, Mota et al, and Efthymiopoulos et al [40,50,51] reported the fat content in silverskin (Coffee canephora) reaching 18.2 ± 0.1 g.kg −1 . Costa et al [12] reported that silverskin contains 24.2 g.kg −1 of fat.…”
Section: Fat and Fatty Acidmentioning
confidence: 99%
“…As evidenced by Al-Hamamre et al [48], the higher yield was also affected by the increased duration of the extraction, which in the case of Soxhlet can take up to 24 h. However, according to the results (Figure 1), the method that prevailed over the other two was ASE, since the yields of all three solvents were higher than those obtained with either Soxhlet extraction or UAE. These results can be assigned to the fact that extraction was performed under higher than atmospheric pressure and a temperature close or above solvent's boiling point [39]. Thus, even though the temperature was high, the pressure kept the solvent in a liquid state and facilitated the extraction of compounds located within the matrix pores [40].…”
Section: Preliminary Experimentsmentioning
confidence: 99%
“…Depending on the combination of temperature and pressure, water can change polarity as its dielectric constant is altered. Thus, water can solubilize a wide range of compounds of both medium and low polarity [39,49].…”
Section: Preliminary Experimentsmentioning
confidence: 99%
See 1 more Smart Citation